Transcriptomic and splicing changes underlying tomato responses to combined water and nutrient stress - Ruggiero, Alessandra; Punzo, Paola; Van Oosten, Michael James; Cirillo, Valerio; Esposito, Salvatore; Costa, Antonello; Maggio, Albino; Grillo, Stefania; Batelli, Giorgia (Frontiers in Plant Science, 2022)
Tomato is a horticultural crop of high economic and nutritional value. Suboptimal environmental conditions, such as limited water and nutrient availability, cause severe yield reductions. Thus, selection of genotypes requiring lower inputs is a goal for the tomato breeding sector. We screened 10 tomato varieties exposed to water deficit, low nitrate or a combination of both. Biometric, physiological and molecular analyses revealed different stress responses among genotypes, identifying T270 as severely affected, and T250 as tolerant to the stresses applied. Investigation of transcriptome changes caused by combined stress in roots and leaves of these two genotypes yielded a low number of differentially expressed genes (DEGs) in T250 compared to T270, suggesting that T250 tailors changes in gene expression to efficiently respond to combined stress. By contrast, the susceptible tomato activated approximately one thousand and two thousand genes in leaves and roots respectively, indicating a more generalized stress response in this genotype. In particular, developmental and stress-related genes were differentially expressed, such as hormone responsive factors and transcription factors. Analysis of differential alternative splicing (DAS) events showed that combined stress greatly affects the splicing landscape in both genotypes, highlighting the important role of AS in stress response mechanisms. In particular, several stress and growth-related genes as well as transcription and splicing factors were differentially spliced in both tissues. Taken together, these results reveal important insights into the transcriptional and post-transcriptional mechanisms regulating tomato adaptation to growth under reduced water and nitrogen inputs.